Hubungan Kepuasan Kerja dan Loyalitas Pada Karyawan - Abraham Rehuel Kosasih; Jimmy Ellya Kurniawan (Universitas Ciputra Surabaya, 2018)
Human resource is one of many important aspects within a company; hence, it is imperative for the company to take the satisfaction and commitment regarding the employees into the account. Employees with a high level of loyalty will bring benefit towards the company. Preceding study shows a positive relation between job satisfaction and employee commitment. As a matter of fact, the relation between job satisfaction and employee commitment is a non-existent. This quantitative study would like to carry out the fact that the relation between job satisfaction and employee commitment exists. The researcher employs the job satisfaction scale used and adapted by Spector (2012) and organizational commitment by Mowdays, Steers, & Porter (1979) as the measurements. The population is taken from the employees working in the sector of hospitality in Bali, Indonesia which, then, become the total population study and the result shows that ρ = 0.705 and p-value = 0.000.